Chronic kidney disease in psoriasis: a cohort study. (20th April 2020) - Conti, Andrea; Giovannini, Lisa; Mandel, Victor Desmond; Odorici, Giulia; Lasagni, Claudia; Bigi, Laura; Pellacani, Giovanni; Cappelli, Gianni
Summary: Background: Psoriasis is a chronic, relapsing disease often associated with comorbidities. While its associations with cardiovascular and metabolic factors have been investigated, little is known about its association with impairment of renal function. Materials and methods: We performed a cohort study of 219 psoriatic patients in which we evaluated chronic kidney disease (CKD) and eGFR as well as albuminuria according to their KDIGO stratification risk criteria. We also evaluated circulating immunoglobulins (IgG, IgA, IgM), C3‐C4 levels and the urinary albumin‐to‐creatinine ratio. We divided the patients into two groups, according to the presence or absence of known and established CKD risk factors. Results: In our population, the risk of CKD was moderate in 17.35 % of patients, high in 5.02 % and very high in 3.66 %. The risk prevalence for CKD was slightly greater in the group without established risk factors than the risk prevalence reported in NHANES 1999–2006. The presence of psoriatic arthritis, duration of psoriasis (≥ 21 years) and magnitude of the PASI score showed a positive correlation with the urinary albumin‐to‐creatinine ratio. Conclusions: We found an association between microalbuminuria and the duration of psoriasis, as well as with psoriatic arthritis. Moreover, patients with microalbuminuria exhibited a higher Kidney Disease Improving Global Outcome stratification risk.